Analysis of Non Perfroming Loans in Indonesia: A Perspective of Market Discipline. - SEPTO HADI WIBOWO (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
The purpose of this research was to analyze the effect of bank specific variables, including Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Return on Asset (ROA), Return on Equity (ROE), and Loan Loss Provision (LLP), and market discipline variables, namely Interbank Deposit Ratio (IDR), Subordinated Debt (SND), and Information Disclosure Index (ID) on Non- Performing Loan (NPL) Ratio. The data used in this study was annual data from 2006 to 2017 (12 years) taken from BUKU 4 Conventional Commercial Banks annual report. This study used multiple linear regression analysis and Ordinary Least Square as the estimator with the help of a computer program, Stata version 14.2, as the main software to process the research data. The results showed that together (simultaneously) the independent variables (CAR, LDR, ROA, ROE, LLP, IDR, and SND) significantly affected the change in the ratio of Non-Performing Loan (NPL). While partially, all of CAR, LDR, ROA, and ROE had significant effect on NPL. CAR and ROE had significant and positive effect, while LDR and ROA had significant and negative effect on NPL. The other 3 variables, including LLP, IDR, and SND, have non- significant effect on NPL. The result indicated that LLP and IDR had non- significant and negative effect, while SND had non-significant and positive effect on NPL. In addition, Information Disclosure Index (DI) variable was not included in the multiple linear regression model because the finding of this study showed that all BUKU 4 Banks got a perfect score for their disclosure index each year troughout 2006 to 2017 period, therefore the analysis for this variable was being done descriptively. In other words, it can be concluded that all BUKU 4 Conventional Commercial Banks already disclose every information required in the disclosure index, therefore, the DI variable can’t be used as a parameter to analyze the effect of market discipline variables on NPL.Keyword: NPL, CAR, ROA, SND, IDR